Investigation of Propyphenazone Molecule by Quantum Chemical Methods - Kebiroglu, Hanifi; Büyük, Öznur; Bulut, Niyazi (Niyazi BULUT, 2022)
Computational chemistry approaches were used to manage the phenazone molecule. The phenazone molecule was optimized at the 3-21G (d) level. The structural parameters were investigated. IR and NMR techniques, which are spectroscopic approaches, were used to determine the structure. The highest occupied molecular orbital (HOMO) energy, the lowest unoccupied molecular orbital (LUMO) energy, hardness (?), softness (?), chemical potential (?), electronegativity (?), electrophilicity index (?), nucleophilicity index (?), the electron accepting power (?+), electron-donating power (?-), and polarizability of the propyphenazone molecule were investigated. NMR spectra for 1H and 13C, as well as UV-Vis spectra, were obtained. HOMO-LUMO and molecular electrostatic potential (MEP) analyses were carried out. The theoretical calculations for the molecular structure and spectroscopy were done using the Gaussian 09 software with HF and 3-211G (d) basis set calculations. The GaussSum 3 software was used to compute the density of state (DOS).
Keywords: Metrology; Applied and Industrial Physics; Metroloji; Uygulamalı ve Endüstriyel Fizik